Analysis Of Physics Problem Solving In The Perspective Of Self Efficacy and Adversity Quotient - Napis Napis (Formatif: Jurnal Ilmiah Pendidikan MIPA, 2018)
This study aims to determine the effect of self efficacy, and adversity quotient on Physics problem solving. This research is based on the low problem solving of Physics, caused by self-efficacy and adversity quotient. The research used a quantitative approach, survey method with path analysis technique. A sample of 100 students selected at random. The data collection technique used questionnaires to measure self-efficacy, and adversity quotient, while the essay question was used to measure the Physics problem solving on the electric current matter. The result of the path coefficient calculation in the path analysis model is more than 0.05 which means significant. Physics problem-solving path coefficient on self-efficacy 0.222, with contribution 4.92%. Physics problem-solving coefficient on adversity quotient is 0.290 (8.41%). The contribution of self-efficacy to adversity quotient is 7.18% with path coefficient 0.268. The result shows that adversity quotient has a more dominant influence on Physics problem-solving.The results of the study show that: (1) self-efficacy has a positive effect on Physics problem solving, (2) adversity quotient has positive effect on Physics problem solving, (3) self-efficacy has positive effect on adversity quotient, and (4) self-efficacy gives an indirect effect on Physics problem solving through adversity quotient.